Inhabitation policy and quality of the house. reflections on the habitability of the house of low cost in bogotá (2006)
Colombia initiated the decade of the Nineties with a substantial change in its habitudinal policy, stopping to be a promotional State of housing to become into a regulating State of its market without quality parameters that guide their performance. This change has had repercussions that not yet have been evaluated in order to guide the public policies and to improve their efficiency, reason why habitability problems persist which surpass the scale of the house and extend to the construction of the city, and that they demand public, concrete and urgent actions. This affirmation comes from the results obtained in recent studies on the subject, studies that have been made in urban developments of low cost housing in Bogota.